Pengaruh Pengalaman Nasabah Dalam Penggunaan MBanking Terhadap Loyalitas Nasabah Bank Syariah Indonesia (Studi Kasus Masyarakat Sei Mencirim) - Syahira, Tira; Indra, Ahmad Perdana; Anggraini, Tuti (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this research is to determine whether a company's ability to retain its current customers is more important than its ability to acquire new customers. BSI wants to increase customer satisfaction and service quality by growing customer loyalty through mobile banking. Even though many BSI clients already have BSI Mobile, not all of them make full use of it. Therefore, the level of customer loyalty when using BSI Mobile is not too high. This is based on consumer interviews with BSI mobile banking users which show that consumers often decide to make transactions via BSI Mobile. The reason is that BSI Mobile is more user friendly and convenient; all you need is a smartphone to use it anytime, anywhere. For customers who decide not to use BSI Mobile for transactions due to lack of security, increased vulnerability to fraud, and ease of hacking. The aim of this research is to analyze and assess how customer experience and service quality influence BSI mobile banking customer loyalty, both partially and simultaneously. A quantitative approach was used in this research. This data was collected through survey research techniques on BSI customers who use mobile banking services. Customer loyalty and service quality in BSI mobile banking are positively and significantly influenced by customer experience, according to research findings